Triangular models of commutative systems of linear operators close to unitary operators - Hatamleh, R.; Zolotarev, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
Triangular models are constructed for commutative systems of linear bounded operators close to unitary operators. The construction of these models is based on the continuation of basic relations for the characteristic function along the general chain of invariant subspaces.